A Theoretical and Experimental Kinetic Investigation of the ROP of L, L‐Lactide in the Presence of Polyalcohols. Issue 1 (November 2013) - Karidi, Konstantina; Pladis, Prokopios; Kiparissides, Costas; Moritz, Hans‐Ulrich; Pauer, Werner
Summary The present work deals with the experimental and theoretical investigation of the ring‐opening polymerization of L, L‐lactide with stannous octoate as a catalyst for the production of high molecular weight polymers with improved physical and mechanical properties. The polymerization of L, L‐lactide was experimentally studied at various temperatures and different monomer to initiator concentration ratio values. Subsequently, co‐initiators with different number of hydroxyl groups (i.e., 1, 4‐butanediol, glycerol, di‐trimethylolpropane and polyglycidol) were utilized to obtain branched or star shaped polymers. A comprehensive mathematical model was developed based on a detailed kinetic mechanism to predict the dynamic evolution of monomer conversion and molecular weight averages (i.e., Mn, Mw of PLLA). The predictive capabilities of the mathematical model are demonstrated by a direct comparison of model predictions with literature and new experimental data on monomer conversion as well as number and weight average molecular‐weight of PLLA.